Hypercalciuria in Postmenopausal Women With Reduced Bone Mineral Density Is Associated With Different Mineral Metabolic Profiles: Effects of Treatment With Thiazides and Anti-resorptives - Nicoli, Federico; Dito, Giorgia; Guabello, Gregorio; Longhi, Matteo; Corbetta, Sabrina (Frontiers in Medicine, 2021)
Hypercalciuria may represent a challenge during the workup for osteoporosis management. The present study aimed: 1) to describe the phenotype associated with hypercalciuria in vitamin D-sufficient (serum 25OHD > 20 ng/ml) osteopenic/osteoporotic patients; 2) to analyze the effects of thiazides and anti-resorptive drugs on urine calcium excretion (UCa), mineral metabolic markers and bone mineral density. Seventy-seven postmenopausal women with hypercalciuria (UCa>4.0 mg/kg body weight/24h on two determinations) were retrospectively evaluated in a real-life setting. Median UCa was 5.39 (4.75-6.70) mg/kg/24h. Kidney stones occurred in 32.9% of patients, whose median UCa was similar to that of patients without kidney stones. Clustering analysis considering the three variables serum calcium, phosphate and parathormone (PTH), identified two main clusters of hypercalciuric patients: cluster 1 (n=13) included patients with a primary hyperparathyroidism-like profile, suggesting a certain degree of autonomous PTH secretion from parathyroid glands, while within cluster 2 (n=61), two subgroups were recognized, cluster 2A (n=18) including patients with relatively elevated PTH and normophosphatemia, and cluster 2B (n=43) including patients with normal mineral profile. After a follow up of 33.4±19.6 months, 49 patients treated with thiazidic diuretics (TZD) were reevaluated; 20 patients were treated with hydrochlorothiazide (HCT; 12.5-37.5 mg/day), 29 with indapamide (IND; 1.50-3.75 mg/day). Any significant difference could be detected in all the parameters both in basal and treated conditions between patients treated with HCT or IND. TZD induced a mean 39% reduction in UCa and 63.3% of patients obtained UCa<4.0 mg/kg/24h, independently of their mineral metabolic profile. Moreover, TZD induced a significant decrease of PTH levels. TZD-treated patients normalizing urine calcium excretion experienced increases in bone mineral densities when concomitantly treated with anti-resorptives, while any gain could be observed in TZD-treated patients with persistent hypercalciuria. Finally, multiple regression analysis showed that urine calcium excretion reduction was at least in part related to denosumab treatment. In conclusion, in postmenopausal osteoporotic women, hypercalciuria is associated with kidney stones in about one third of patients and with a wide range of impaired PTH secretion, determining a diagnostic challenge. TZD efficiently reduce urine calcium excretion and normalization contributes to increase anti-resorptives positive effect on bone mineral density.